Numerical Study on Novel Design for Compact Parallel-Flow Heat Exchanger with Manifolds to Improve Flow Characteristics - Byunghui Kim; Kuisoon Kim; Seokho Kim (Energies, 2020)
Parallel flow heat exchangers with manifolds are widely used in various industries owing to their compact size and ease of application. Research has been conducted to understand their flow characteristics and improve flow distribution and pressure drop performance; however, it is difficult to derive generalized improvements under different conditions for each application. This study proposes a novel design to improve the flow characteristics of a compact heat exchanger with a sudden expansion area of a dividing manifold and uses computational fluid dynamics simulation to verify it. The abrupt cross-sectional area change in the dividing manifold induces a jet flow near the entry region, which causes the flow maldistribution of the first few parallel tubes. To improve the efficiency of the dividing manifold, simple and novel designs with a converging-diverging area in the manifold header have been proposed. Parametric studies on the novel designs show improvements of up to 37.5% and 52.0% flow uniformity and 2.65% and 0.74% pressure drop performance for U- and Z-types, respectively, compared to the base model. Thus, the simple and easily fabricated quadrilateral shape can improve the flow maldistribution and pressure drop caused by a dividing manifold with a sudden area expansion.